Tumor Necrosis Factor Alpha and Interleukin-6 Facilitate Corneal Lymphangiogenesis in Response to Herpes Simplex Virus 1 Infection - Bryant-Hudson, Katie M. (J Virol, 2014)
Herpes simplex virus 1 (HSV-1) is a common human pathogen of clinical significance due to its association with vision impairment and encephalitis. In a mouse model of ocular neovascularization, we have previously shown that HSV-1 elicits the genesis of lymphatic vessels into the cornea proper through epithelial cell expression of vascular endothelial growth factor A (VEGFA) dependent upon expression of VEGFR2 during acute infection. We hypothesized that other factors may be involved in lymphangiogenesis, with proinflammatory cytokines as the leading candidates. In the absence of infection or inflammation, intrastromal administration of tumor necrosis factor alpha (TNF-α) coupled with VEGFA elicited lymphatic vessel genesis significantly above either factor alone as well as a vehicle control. Consistent with this observation, anti-TNF-α antibody (Ab) blocked HSV-1-mediated corneal lymphangiogenesis within the first 5 days postinfection. However, TNF-α-deficient (TNF-α(−/−)) mice displayed a level of corneal vessel growth similar to that shown by wild-type (WT) controls. To investigate the likely redundant nature of cytokines, PCR array analysis of HSV-1-infected TNF-α(−/−) mice was conducted, and it revealed several factors elevated above those found in HSV-1-infected WT mice, including interleukin-1β (IL-1β), platelet-derived growth factor, angiopoietin 2, insulin-like growth factor 2, and IL-6. Subconjunctival administration of neutralizing Ab to IL-6 blocked lymphangiogenesis in TNF-α(−/−) mice. Whereas the cornea levels of IL-6 were significantly reduced, there was no appreciable change in the level of IL-1β or other proangiogenic factors analyzed. Collectively, the results suggest in addition to VEGFA, TNF-α and IL-6 promote and likely synergize with VEGFA in corneal lymphangiogenesis during acute HSV-1 infection. IMPORTANCE We have identified at least two proinflammatory cytokines expressed locally that are involved in the genesis of lymphatic vessels in the normally avascular cornea in response to HSV-1 infection. This finding provides the basis to target IL-6 and TNF-α as additional proangiogenic factors in the cornea during the development of herpetic stromal keratitis as a means to alleviate further neovascularization and tissue pathology associated with the host immune response to the pathogen.